Facebook, reputational crisis and escape to the metaverse - Costa-Sánchez, Carmen (Anuario ThinkEPI, 2022)
Facebook was involved in one of the most important scandals of recent years owing to its legal, political, social, and ethical implications. The Cambridge Analytica case, which has still been insufficiently addressed as an object of study in its full complexity, highlights the incalculable value of user data and the potential for their manipulation. This marked the beginning of the decline of Facebook´s reputation owing to a combination of negative situations and that has continued since. This paper analyzes the case and its implications in terms of the concepts of reputation and crisis, highlighting the importance of a positive image and its impact on different stakeholders, and points to the rebranding as Meta as a false closure of a crisis of confidence that continues today.
Keywords: Facebook; Meta; Crisis; Reputation; Communication; Trust; Social networks; Metaverse